Correlation of the levels of DNA-binding inhibitor Id3 and regulatory T cells with SLE disease severity. Issue 113 (September 2020) - Liu, Chen; Yu, Sen; Jin, Rong; Long, Yan; Lu, Songsong; Song, Ying; Sun, Xiuyuan; Sun, Xiao-Hong; Zhang, Yu
Abstract: E proteins, a subset of basic helix-loop-helix (bHLH) proteins, are transcription activators and their functions are inhibited by DNA-binding inhibitor (Id) 1–4. Studies have shown that Treg levels are decreased in Id3 knockout mice. Mice over-expressing Id1 in CD4 T cells possessed a greater number of regulatory T cells (Treg) and exhibited attenuated experimental autoimmune encephalomyelitis (EAE). The significance of Id proteins in human systemic lupus erythematosus (SLE) remains unclear. In this study, we systematically analyzed Id transcription in naïve, memory CD4 cells and regulatory T cells in peripheral blood mononuclear cells (PBMCs) in patients with active or inactive SLE. In parallel, Treg subsets in PBMCs were analyzed using different strategies. Id expression levels were correlated with Treg numbers as well as clinical indicators. We found that Id genes expressed in human peripheral CD4 cells were mainly Id2 and Id3 . Id3 levels were significantly elevated in CD4 + CD25 hi T cells of patients with active SLE. Likewise, Id3 levels were positively correlated with increased CD4 + FoxP3 + and CD4 + Helios + FoxP3 + Treg cells in these patients. Id3 levels were found to be positively correlated with erythrocyte sedimentation rate (ESR), lupus anticoagulant (LAC), ribosomal antibody and SLE Disease Activity Index (SLEDAI) in patients with active SLE. Mice overexpressing Id1 in CD4 + T cells possessed significantly higher Treg levels in spleen and lower autoantibody concentrations in serum. Our results suggest that during the pathogenesis of SLE, up-regulation of Id3 can promote Treg differentiation to play an inhibitory effect on autoimmune responses. Highlights: Levels of inhibitor of DNA-binding (Id) 3 in Treg cells of active SLE patients are significantly increased. Id3 levels positively correlate with Treg frequencies in patients with active SLE. Id3 levels positively correlate with SLEDAI scores in patients with active SLE. Id-overexpressed mice produce less autoantibodies in the pristane-induced lupus model.